Pengaruh Pemanfaatan Aplikasi Google Classroom Terhadap Hasil Belajar Siswa di SMK Kartika 1-2 Padang (Study Mata Pelajaran Jurusan Otomatisasi Dan Tata Kelola Perkantoran Pada Saat Daring) - Fitri, Fitri; S, Armida (Jurnal Salingka Nagari, 2022)
The raw data types obtained by distributing questionnaires in the form of Google Sheets to X, XI and XII office management automation students at SMK Kartika 1-2 Padang have specified criteria. The results show that the use of the Google Classroom app and the benefits of the Google Classroom app simultaneously have a significant impact on student learning outcomes. using the Google Classroom app had a huge positive impact on learning outcomes. Between students , the benefits of the Google Classroom app had a positive and significant impact on student learning outcomes. The use and benefits of the Google Classroom app had a 24% impact on student learning outcomes in the Department of Office Automation and Control, Department of Office Automation and Control, SMK Kartika 1-2 Padang.